Leaders of the Opposition
IX, 282 p.
Keywords: Timothy Heppell brings together a renowned group of contributors to consider the role of the Leader of the Opposition in British Politics. The book argues that the neglect of opposition studies needs to be addressed, especially given the increasing importance attached to the performance the Leader of the Opposition in the British political system.